Correlates of Attitudes Toward Academic and Physical Inclusive Practices for Students with Disabilities and Selected Leadership Behaviors Among Middle School Principals in North Carolina - Houser, Mary A.; Dickens, Virginia; Hicks, Terence (Journal of the American Academy of Special Education Professionals, 2011)
The purpose of the study was to examine the relationship between attitudes toward academic and inclusive practices for students with disabilities and selected leadership behaviors (transformational and transactional) among principals in North Carolina. Participants for this study were randomly selected middle school principals from public schools in North Carolina. This study used a one-group, correlational design, using two instruments. The results of this study found a significant relationship between academic and physical inclusive practices and transformational leadership behaviors, r (75) =0.320, p